Debt Management Performance Assessment : Dominica - World Bank (World Bank, Washington, DC, 2020)
The World Bank and the Eastern Caribbean Central Bank (ECCB) undertook a comprehensive assessment of the debt management (DeM) functions of the Government of Dominica (GoD) from June 18 to 22, 2018.The main outcomes of the debt management performance assessment are as follows: The assessment indicates that legal framework includes clear authorization for the Minister of Finance to borrow and issue loan guarantees on behalf of the Government. However, authorization to issue bonds in the regional market is not clearly defined.legal framework is fragmented and does not include borrowing purposes. The Debt Management Unit (DMU) is the principal guarantee entity but the borrowing operations involve more entities and are not well coordinated.Reasonably reliable debt service forecasts are produced by the DMU, but in-house debt sustainability analysis (DSA) is not undertaken. A staff in Macroeconomic Unit within the MoF has received training in the use of DSA framework and plans to undertake the exercise in-house in the coming fiscal year.Cash flows are forecasted on a monthly basis, but not submitted to the ECCB for liquidity management purposes. The Government has access to a well-developed Regional Government Securities Market (RGSM), but the potential has not been fully reaped, since Treasury bills (T-bills) are also issued locally with less advanced techniques, implying significant exposure to operational risks.Monthly detailed cash flow forecasts are prepared by the Accountant General´s Office (AGO) which could be used to guide upcoming budget allocation and short-term T-bill issuance for cash management purposes.The DMU is maintaining complete government debt and guarantees’ records which are updated quickly due to well-developed contacts with creditors and projects.The DMU has developed a draft procedures manual but it does not cover all DeM procedures and it has not been finalized. The DMU staff capacity is not sufficient and the work is not organized with adequate segregation of duties.